Confronting Moral Responsibility and Adiaphorization: Bauman’s Postmodern Ethics through The Zone of Interest (2023) - Kadiroğlu, Murat; Akan, Adnan (Problemos, 2025)
This article explores Zygmunt Bauman’s view on moral responsibility, in a fluid world, focusing on the postmodern perspective on morality which is not based on ethical codes. The aim is to demonstrate how modern morality, influenced by power structures, is shaped by adiaphoric regulations that distort the individual’s relationship with the Other. This is achieved by first examining Bauman’s concept of adiaphorization, and then briefly reading it alongside Agamben’s homo sacer while analysing Jonathan Glazer’s film, The Zone of Interest, as a concrete example of moral indifference to illustrate how adiaphorization operates within ethical frameworks. The study argues that mechanisms such as the Holocaust were facilitated not only through the ‘suspension of law’ but also through adiaphorization, ‘suspension of morality’ – not a Baumanian term but our coinage – via what is here termed the destabilization of responsibility: the structural dispersal and fragmentation of moral accountability.